2017
DOI: 10.1001/jama.2017.11463
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Routine Low-Dose Oxygen Supplementation on Death and Disability in Adults With Acute Stroke

Abstract: IMPORTANCE Hypoxia is common in the first few days after acute stroke, is frequently intermittent, and is often undetected. Oxygen supplementation could prevent hypoxia and secondary neurological deterioration and thus has the potential to improve recovery. OBJECTIVE To assess whether routine prophylactic low-dose oxygen therapy was more effective than control oxygen administration in reducing death and disability at 90 days, and if so, whether oxygen given at night only, when hypoxia is most frequent, and oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 33 publications
2
90
1
9
Order By: Relevance
“…Based on supplementary analysis, the authors of the systematic review concluded that treatment with oxygen could become unfavourable in acutely ill patients if resulting in an SpO 2 above 94%‐96%. However, this specific upper target of SpO 2 is not supported by the trials with the highest weight in the mortality analysis, as these studies effectively all investigated normoxaemia vs hyperoxaemia with SpO 2 above 94%‐96% in the conservative oxygenation groups. Nevertheless, this upper SpO 2 target has recently been implemented in a clinical guideline on oxygen therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Based on supplementary analysis, the authors of the systematic review concluded that treatment with oxygen could become unfavourable in acutely ill patients if resulting in an SpO 2 above 94%‐96%. However, this specific upper target of SpO 2 is not supported by the trials with the highest weight in the mortality analysis, as these studies effectively all investigated normoxaemia vs hyperoxaemia with SpO 2 above 94%‐96% in the conservative oxygenation groups. Nevertheless, this upper SpO 2 target has recently been implemented in a clinical guideline on oxygen therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Randomised clinical trials outside the ICU have found that oxygen supplementation to non‐hypoxic patients with acute myocardial infarction does not change long‐term outcome, and may increase myocardial damage and thus, the preferred liberal approach may not be beneficial. Trials on oxygen supplementation in non‐hypoxic patients with acute stroke outside the ICU have failed to show long‐term benefit of oxygen supplementation . Therefore, no evidence supports a more liberal approach in patients with cerebral ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence in patients with initially higher SpO 2 (>92%) is more certain because most patients in the trials had a baseline SpO 2 above 92%. For example, in the largest of eight trials of patients with stroke only 240 patients (3.1% of 7677 participants) had an initial SpO 2 of 90-93.9% 16. For myocardial infarction, six trials enrolled 7898 patients: in the largest trial, 1062 patients (16.0%) had an initial SpO 2 ≤94% 17.…”
Section: The Evidencementioning
confidence: 99%